The roles of environmental conditions and spatial factors in controlling stream macroalgal communities - Branco, Ciro Cesar Zanini [UNESP]; Bispo, Pitágoras da Conceição [UNESP]; Peres, Cleto K.; Tonetto, Aurelio F. [UNESP]; Branco, Luis H. Z. [UNESP] (Springer, 2014)
In the last three decades, several studies have suggested that the structure of stream macroalgal communities is shaped by local environmental variables, but some recent papers have shown that the relevance of the environment on these communities may be overestimated. Using Partial Redundancy Analysis (pRDA), we analyzed macroalgal communities (considering all macroalgae and Phyla Chlorophyta, Cyanobacteria, and Rhodophyta individually) from 105 streams in southern Brazil to test the hypothesis that the relative contributions of the environment and space on the taxonomic composition of these communities is mainly determined by the biological traits and dispersal mechanisms typical for each group. The pRDA showed that the taxonomic composition of the entire community and green algae were explained by both space and environment, whereas for cyanobacteria, only the environment was significant, and for red algae, only space was significant. These divergences in the relative contribution among algal phyla were consistent with our initial hypothesis and can be ascribed to the differences in the ecological features of each group. Our results also support the idea that the community structure of organisms with low dispersal is influenced more significantly by spatial processes, whereas for organisms with high dispersal the local environmental variables are more influential.
Keywords: Metacommunity; Variation partitioning; Partial redundancy analysis (pRDA); Dispersal ability; Spatial structure; Stream macroalgae